Evaluation of the Forensic Patients Presenting to the Emergency Department and Legal Reports - Tanzer Korkmaz; Nurettin Kahramansoy; Zerrin Erkol (Haseki Tıp Bülteni, 2012)
Aim: In this study, the aim was determining the profile of the forensic cases in our city and investigating the relationship between the type of forensic events and the temporary or definite reports that were prepared in these cases. Methods: Medical documents and forensic reports of the patients, who had presented to the emergency department at Abant Izzet Baysal University Research and Application Center, between 01.01.2008-31.12.2009, were analyzed retrospectively. Results: Forensic patients constituted 7.01% of all cases in the emergency department. Majority of patients were male (66.4%), the mean age was 32.41±17.83. The most common type of forensic event was motor vehicle accident (53,7%). Forensic events were reported to occur mostly during daytime, in the 12.00-18.00 hour period. Hospital arrival time was 82.63 minutes in average, length of stay in emergency department was 1-4 hours and, 30.6% of the patients were discharged without any consultations. Discharge rate from the emergency department was 68.5%. The rate of temporary reports prepared for patients who were discharged from emergency service were as high as 69.8% and was significantly higher than that of definite reports. Conclusion: Generalization of the pre- and post-graduate training programs for the physicians working in emergency department can increase the number of definite reports in forensic cases. (The Me di cal Bul le tin of Ha se ki 2012; 50: 14-20)